Role of multidetector computed tomography angiography in evaluation of peripheral arterial disease - Kumar, Rakesh; Taneja, Anil (International Journal of Research in Medical Sciences, 2020)
Background: Diagnostic imaging plays an important role in the evaluation of peripheral arterial disease. Many imaging modalities are available ranging from conventional modalities to the cross-sectional modalities like Doppler ultrasound, DSA, CT and MRI. The main principles of imaging are to characterize the all lesions detected including type of plaques, no. of lesions, length of stenosis, diameter of vessel in pre-stenotic and post-stenotic segments, degree of wall calcification, assisting in pretreatment planning with respect to route of access, selection of balloon and demonstrates size, extent, neck dimention, and presence of thrombosis in cases with aneurysm. Methods: A Cross-sectional observational study was done in 30 patients. Clinically suspected patients of peripheral arterial disease based on history, sign and symptoms and patients diagnosed with peripheral arterial disease on color doppler were included in our study. Both modalities were compared for detecting the occlusion and stenotic segments. Results: A total of 476 vessel segments were imaged by both modalities. When all arterial segments were considered, MDCTA detected stenosis or occlusion lesions in 30% of arterial segments, versus 18.8% compared to DUS. MDCTA showed 9.8% (95% CI:[4.3%, 15.3%]) more lesions than DUS when all arterial segments were considered together, 11.2% (95% CI: [2.7%, 22.1%]) more lesions when only the iliac arteries were compared, 9.1% (95% CI: [3.2%, 17.2%]) more lesions when only the femoropopliteal arteries were compared, 8.9% (95% CI: [1.5%, 16.3%]) more lesions when only infrapopliteal arteries were compared and 13% (95% CI: [2.6%, 25.4%]) more lesions when only the upper limb arterial segments were compared, (p <0.05 for all comparisons). Conclusions: MDCTA may be used as a screening tool in patients with peripheral arterial disease as it is a non-invasive and more accurate modality when compared to DUS and plays important role in management.